(untitled) (Journal of the College of Basic Education, 2026)
This study examines the syntactic structures of interrogative and vocative forms, clarifying their semantic meanings and rhetorical purposes within the context of prophetic praise poetry through the poem “The Jiyad Preludes in the Praise of Sayyid al-Jiyad.” The study focuses on uncovering the impact of grammatical tools in expressing exaltation, wonder, and emotional intensity, and how these tools move from their original literal meanings to deeper rhetorical meanings that serve poetic significance.The research traces rhetorical interrogation for purposes such as glorification, admiration, denial, and longing, as well as vocative expressions that evoke love, yearning, and spiritual presence. This is done to demonstrate how grammatical tools influence poetic meaning and how grammatical rules are transformed into expressive emotional and devotional instruments, revealing the poet’s skillful employment of language.The study aims to clarify the relationship between syntactic form and semantic meaning and to demonstrate the poet’s ability to employ interrogative and vocative tools as artistic techniques that influence the recipient and deepen the aesthetic and religious understanding of the text.The study adopted poetic texts as its corpus, monitoring the use of interrogative and vocative tools. The number of interrogative tools reached nine, occurring twenty-five times, while vocative tools amounted to three, appearing twenty-two times.The research topic is addressed through an introduction and a methodological preface that includes: defining al-Tahani and the Jiyad Preludes, followed by two main sections. The first discusses vocative forms and their applications in the Jiyad Preludes, while the second addresses interrogative forms and their applications in the same work.The study follows a descriptive-analytical methodolog. Among the most important findings of the study is that the poet most frequently employs interrogative tools in the form of particles and nouns, while the use of vocative tools is largely limited to “Ya” and the hamzah.